Correlation of AISI and PLR as Systemic Inflammatory Markers with Hospitalization Duration in Pediatric Typhoid Fever Patients - Metana Puspitasari; Muhammad Yusuf; Zulfiona Dianes; Safari Wahyu Jatmiko (JURNAL IMPLEMENTA HUSADA, 2026)
Introduction: Typhoid fever remains a major public health problem in developing countries, including Indonesia, with a high incidence among children requiring hospitalization. Simple systemic inflammatory markers such as the Aggregate Index of Systemic Inflammation (AISI) and Platelet Lymphocyte Ratio (PLR) are increasingly studied because they can be calculated from routine blood tests and may serve as clinical indicators. Method: This retrospective cross-sectional study involved 57 pediatric patients with typhoid fever at PKU Muhammadiyah Sampangan Hospital, Surakarta, who met the inclusion and exclusion criteria. Data were analyzed using the Kolmogorov–Smirnov test for normality and the Spearman correlation test to evaluate associations between variables. Result : The results showed no significant correlation between AISI and the length of hospitalization (p = 0.994; p 0.05) or between PLR and the length of hospitalization (p = 0.320; p 0.05). Discussion: These findings indicate that AISI and PLR have no prognostic value in predicting hospitalization duration in pediatric typhoid fever patients. Further studies with larger sample sizes, prospective designs, and the inclusion of additional inflammatory biomarkers are needed to validate and strengthen these findings.